Geometric Mean with Pythagorean Fuzzy Transportation Problem - et. al., S.Krishna Prabha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transportation algorithm is one of the powerful configurations to afford the retail to the client in proficient deportment. Recently to deal with ambiguity in optimization problems like transportation problem, Pythagorean fuzzy set (PFS) theory is utilized. Compared with fuzzy sets and intustionistic fuzzy sets, PFS are widely used for modeling haziness and indistinctness. PFSs have meaningful applications in many different fields. Various investigators have introduced different methods like North West corner method, least cost method, Vogel’s approximation method, heuristic method etc, to crack the fuzzy transportation problems. In this work geometric mean technique is introduced to resolve a Pythagorean fuzzy transportation problem (PFTP) and an algorithm of the suggested method is presented. A numerical example is illustrated with the new technique and the end result acquired through this method is compared with the extant methods. This suggested technique provides an optimal resolution.